Marketing performance measurement: evolution of research and practice. (2nd November 2004) - Clark, Bruce H.; Ambler, Tim
This article reviews the evolution of marketing performance measurement from both research and practitioner perspectives. We find four historical research stages that have evolved in sequence but now continue concurrently, and explore how firms evolve their use of marketing performance measures. Practitioners increasingly regard effectiveness as more important than efficiency in marketing performance. The paper extrapolates that evolution to suggest future directions for practitioners. Identifying the impact of performance measurement systems over time is a critical issue for both research and improved practice.